Bimbingan Kelompok dengan Metode Storytelling untuk Penanaman Sikap Berbuat Baik kepada Teman Sebaya - Visca Robi’atus Syarifah (Scidacplus, 2025)
This study aims to examine the effectiveness of group guidance using the storytelling method in fostering prosocial behavior among early childhood students at RA Al-Fatih Palembang. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research subjects consisted of 10 children in class B1, selected through purposive sampling. The study focused on key indicators of prosocial behavior, including sharing, helping others, and apologizing. The findings revealed that before the intervention, children tended to display egocentric behaviors, such as unwillingness to share, competition over toys, and a lack of concern for peers. However, after participating in six sessions of group guidance integrated with storytelling, significant positive behavioral changes were observed. Children demonstrated increased willingness to share, help others, express empathy, and resolve conflicts by apologizing and forgiving peers. The storytelling method proved to be an effective and engaging approach in facilitating the internalization of moral values through narrative experiences. It not only enhanced children's understanding of prosocial concepts but also promoted the application of these values in their daily social interactions. In conclusion, group guidance combined with storytelling is an effective strategy for developing prosocial behavior in early childhood education settings. This study highlights the importance of using creative, interactive, and value-based approaches in counseling services to support children's social and emotional development.